2023
DOI: 10.1108/jic-07-2023-0157
|View full text |Cite
|
Sign up to set email alerts
|

Green intellectual capital and competitive advantage: the moderating role of corporate philanthropy during COVID-19

Muhammad Akram Naseem,
Enrico Battisti,
Antonio Salvi
et al.

Abstract: PurposeThis study examines the relationship between green intellectual capital (GIC) and competitive advantage (CA) and proposes the moderating role of corporate philanthropy types (cash, in-kind and both) during the COVID-19 pandemic. In particular, this study investigates the types of corporate philanthropy, strengthening the link between GIC and CA for Chinese listed firms during a pandemic.Design/methodology/approachCross-sectional data were collected from 248 chief executive officers (CEOs) of Chinese fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…However, achieving this has become very challenging in the twenty-first century. Literature indicates that a firm's competitiveness relies on its capacity to acquire unique and eco-friendly resources (Almansour, 2024;Khan et al, 2024a;Naseem et al, 2024). Given this, connecting GIC with OA can offer useful insights.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…However, achieving this has become very challenging in the twenty-first century. Literature indicates that a firm's competitiveness relies on its capacity to acquire unique and eco-friendly resources (Almansour, 2024;Khan et al, 2024a;Naseem et al, 2024). Given this, connecting GIC with OA can offer useful insights.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Choudhary and Datta (2023) found that such organizations are more successful in rewarding their workforce for providing creative and unique ideas. Literature indicates that organizations that are well-versed in adapting to environmental uncertainty and support their human resource in exercising their creative faculties are more likely to come up with novel ideas and procedures that support ecological sustainability (Choudhary and Datta, 2024;Khan et al, 2024a;Naseem et al, 2024). EGC may help transform knowledge into creative and sustainable behaviors as a bridge between OA and ECB.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior hospitality research also concentrates on pragmatic investigations of GIC in social interaction (Haldorai et al ., 2022), knowledge sharing and GPIP (Bahrami et al ., 2012), reflecting the growing significance of developing and maintaining competitive advantage. GIC contributes favorably to competitive advantage when such an association is connected to its capacity for problem-proof identity and green knowledge sharing (GKS) (Naseem et al ., 2023). By analyzing the function and significance of GIC within the hotel sector in Pakistan, this study seeks to bridge this research gap.…”
Section: Introductionmentioning
confidence: 99%